2022
DOI: 10.3389/fpls.2022.973388
|View full text |Cite
|
Sign up to set email alerts
|

Biomass production and nutrient use efficiency in white Guinea yam (Dioscorea rotundata Poir.) genotypes grown under contrasting soil mineral nutrient availability

Abstract: Yam (Dioscorea spp.) is of great importance to food security, especially in West Africa. However, the loss of soil fertility due to dwindling fallow lands with indigenous nutrient supply poses a challenge for yam cultivation. This study aimed to determine shoot and tuber biomass and nutrient use efficiency of white Guinea yam (Dioscorea rotundata) grown under low- and high-NPK conditions. Six white Guinea yam genotypes were used in field experiments conducted at Ibadan, Nigeria. Experiments were conducted with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(9 citation statements)
references
References 30 publications
1
8
0
Order By: Relevance
“…The experimental plots had low-fertility soil [26], to which chemical fertilisers were applied to increase yam tuber yields. Plant responses to fertilisation varied among the genotypes tested (Table 2), suggesting that the effect of fertilisers on tuber yield can be genotype-specific, although these results were consistent with those reported in previous studies [30][31][32][33][34]. The fertiliser had different effects on fresh and dry tuber weights among the genotypes (Table 2); Danacha, Ojuiyawo, and TDa0200012 responded positively to fertilisation, which was predicted to improve productivity if applied to low-fertility soil conditions.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The experimental plots had low-fertility soil [26], to which chemical fertilisers were applied to increase yam tuber yields. Plant responses to fertilisation varied among the genotypes tested (Table 2), suggesting that the effect of fertilisers on tuber yield can be genotype-specific, although these results were consistent with those reported in previous studies [30][31][32][33][34]. The fertiliser had different effects on fresh and dry tuber weights among the genotypes (Table 2); Danacha, Ojuiyawo, and TDa0200012 responded positively to fertilisation, which was predicted to improve productivity if applied to low-fertility soil conditions.…”
Section: Discussionsupporting
confidence: 90%
“…The fertiliser had different effects on fresh and dry tuber weights among the genotypes (Table 2); Danacha, Ojuiyawo, and TDa0200012 responded positively to fertilisation, which was predicted to improve productivity if applied to low-fertility soil conditions. It is suggested that Danacha, Ojuiyawo, and TDa0200012 exhibit superior Fertiliser absorption capacity compared to other genotypes, resulting in enhanced nutrient uptake and, consequently, higher tuber yields [32,34].…”
Section: Discussionmentioning
confidence: 99%
“…The six white Guinea yam genotypes (S004, S020, S032, S042, S058, and S074) were cultivated in the experimental field (N 7°30′, E 3°54′) of the International Institute of Tropical Agriculture (IITA, Ibadan), Nigeria, in 2018. These six genotypes are part of the mini-core collections of white Guinea yam and exhibit varying tuber yield and leaf density [ 6 , 27 ].…”
Section: Methodsmentioning
confidence: 99%
“…Matsumoto et al [ 6 ] reported that these genotypes exhibited identical behavior in field-cultivated experiments and have been used to determine shoot and tuber biomass as well as nutrient use efficiency in white Guinea yam. Consequently, we also used these six genotypes in our study, and the experimental design is presented in Supplementary Table 1 .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation